Penerapan Program PHBS Pada Masa Covid-19 Di Indonesia Sebagai Upaya Pemberdayaan Masyarakat (Literature Review) - Alif Araafi; Arini Salsabila Hasibuan; Friska Dela Oktapiani; Khairani Putri Pratiwi; Salsabila Audina; Ummi Kalsum Nasution; Nisrina Nisrina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. Corona virus or what is known as Covid-19 is a new case of pneumonia that was first reported in Wuhan, Hubei Province. Within a month, this disease had spread to various other provinces in China, Thailand, Japan and South Korea. Implementing clean and healthy living behavior (PHBS) during the Covid19 pandemic can break the chain of virus spread. The aim of this literature review is to see how the Indonesian people implemented clean and healthy living behavior programs during the Covid-19 pandemic. The methodology used to write this article is based on a literature review approach. The journal collection process is based on criteria determined in literature research. Participation criteria are journals published in the last 5 years and indexed in Google Scholar. The results of this article explain the clean and healthy living behavior of the community during the Covid-19 period. Based on the results of this research, it can be concluded that there has been a change in clean and healthy living behavior in Indonesian society during the Covid- 19 period.